A new species of Semaphore gecko Pristurus (Squamata: Gekkonidae) from Mauretania, represents a 4700km range extension for genus - Geniez, Philippe; Arnold, E. Nicholas (Zootaxa, 2006)
A new Semaphore gecko, Pristurus adrarensis, is described from the Adrar Atar region of central Mauritania. It is most closely related to the geographically nearest member of the genus, P. flavipunctatus of northeast Africa and southwest Arabia. P. adrarensis shows an 18% divergence from this species in mitochondrial DNA (cytochrome b) and also differs in being smaller, more depressed and more slender, with the dorsal crest of enlarged scales on the tail not extending forwards beyond the vent. The localities of the new species lie 4700km west of the previously known distribution of Pristurus and the phylogenetic topology of the genus indicates that it represents a westward range extension. The degree of genetic divergence suggests P. adrarensis separated from P. flavipunctatus as much as seven million years ago.